Analysis of Extended Spectrum Beta Lactamase (ESBL) Genes of Non-Invasive ESBL Enterobacterales in Southeast Austria in 2017 - Astrid H. Paulitsch-Fuchs; Nadine Melchior; Theresa Haitzmann; Theres Fingerhut; Gebhard Feierl; Rita Baumert; Clemens Kittinger; Gernot Zarfel (MDPI AG, 2022)
Extended spectrum beta lactamases producing Enterobacteriaceae are a major player in the antibiotic resistance challenge. In general, the situation regarding antibiotic resistance in Austria is very good compared to many other countries. Perhaps this is why there is a lack of data on the distribution of ESBL genes in the clinical setting. The aim of this study was to collect data on ESBL genes from a larger sample of human non-invasive clinical isolates from one region in Austria. In total, 468 isolates from different sample materials isolated at the Medical University of Graz from 2017 were examined. The most frequent organisms were Escherichia coli and Klebsiella pneumoniae. Among the enzymes produced, CTX-M-15 was clearly dominant, exotic ESBLs were only represented by three Proteus mirabilis isolates harboring genes for VEB-6 and one P. mirabilis for CTX-M-2, respectively. Compared to other countries, the results are in line with the expectations. The data help to better classify the many studies from the non-clinical field in Austria and to shift the focus slightly away from the exotic results and sample sites.